2015
DOI: 10.1021/nl503700y
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photochemistry of Ethyl Chloride on Ag Nanoparticles

Abstract: Enhanced photodecomposition of ethyl chloride (EC) adsorbed on SiO2/Si (100) supported silver nanoparticles (Ag NPs) under ultrahigh vacuum (UHV) conditions has been studied in order to assess the potential contribution of plasmonic effects. The cross section for photodecomposition of EC and overall photoyield were found to increase with increasing photon energy regardless of the plasmon resonant wavelength and with Ag coverage without any noticeable particle size effect. The influence of EC-Ag NPs separation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Thus, Au NPs for D = 1.9 nm is more effective for water splitting as shown in Figure . For photodecomposition of ethyl chloride on Ag NPs, the energy alignment of excited electrons and unpopulated adsorbate levels is also central to induce efficient photochemical reactions …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Au NPs for D = 1.9 nm is more effective for water splitting as shown in Figure . For photodecomposition of ethyl chloride on Ag NPs, the energy alignment of excited electrons and unpopulated adsorbate levels is also central to induce efficient photochemical reactions …”
Section: Resultsmentioning
confidence: 99%
“…For photodecomposition of ethyl chloride on Ag NPs, the energy alignment of excited electrons and unpopulated adsorbate levels is also central to induce efficient photochemical reactions. 36 We have also checked the effects for a variation in water orientation. For the water molecule parallel to the surface of Au NP (D = 1.9 nm), the reaction rate of 28 ps −1 at ℏω = 2.36 eV (odd mode) is also larger than that of 27 ps −1 at ℏω = 2.62 eV (even mode) under the same laser illumination as in the Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Jiang et al 130 have reported plasmonic photocatalytic oxidation of benzyl alcohol using Au and Au-Pd NPs loaded TiO 2 nanobelts as catalysts. In addition to the above discussed plasmonic photochemical conversions, hot-electron-induced conversion of aldehydes to esters, 134 and ethyl chloride to ethane or butane 129 have also been reported using supported plasmonic nanoparticles.…”
Section: Hot-electron-induced Chemical Transformationsmentioning
confidence: 99%
“…Recent studies have shown that plasmonic nanostructures could be utilized to drive the chemical reactions through visible light excitation of their localised surface plasmon resonances. 1,46,[114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132] The LSPRs of plasmonic nanoparticles helps to concentrate the low intensity visible light and directs into adsorbed molecules to enhance the rate of chemical transformations in selective manner. 46,114,116,121,127,131 The visible light excitation of surface plasmon resonances of plasmonic nanostructures leads to the increase of local heat as well as generation of hot electrons, which are the two main mechanisms proposed for the plasmon enhanced photochemical organic reactions.…”
Section: Hot-electron-induced Chemical Transformationsmentioning
confidence: 99%
“…It is important to mention that the substrate for the bare nanoparticles (black line in Figure 5A) was a thin RLAD-TiO 2 which is responsible for the SPR absorption shift from 400 to 460 nm. 25 The alumina film does not lead to such a shift, probably as a result of the fact that this oxide has a wider band gap; therefore, its insulating nature does not enable electrons exchange with the AgNPs.…”
Section: Resultsmentioning
confidence: 99%